2015
DOI: 10.1097/md.0000000000001280
|View full text |Cite
|
Sign up to set email alerts
|

Application Value of a 6-Type Classification System for Common Hepatic Artery Absence During Laparoscopic Radical Resections for Gastric Cancer

Abstract: The common hepatic artery (CHA) is an important blood vessel that must be vascularized during D2 lymphadenectomies for gastric cancer. When the CHA is absent, the risk of vascular injury increases.To explore the anatomic classification of CHA absence and its application value in laparoscopic radical resections for gastric cancer.Clinical data were collected prospectively from 2170 gastric cancer patients from June 2007 to December 2013, and the data were analyzed retrospectively. The anatomy of CHA absence was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
(22 reference statements)
0
12
0
Order By: Relevance
“…Gastric cancer is among the most prevalent types of malignant tumor, and has the fourth and second highest rates of incidence and mortality, respectively, among malignant tumors (1,2). Until 2015, the incidence of gastric cancer has increased on a yearly basis and two thirds of all new cases were reported in developing countries, among which China accounted for 42% (3).…”
Section: Introductionmentioning
confidence: 99%
“…Gastric cancer is among the most prevalent types of malignant tumor, and has the fourth and second highest rates of incidence and mortality, respectively, among malignant tumors (1,2). Until 2015, the incidence of gastric cancer has increased on a yearly basis and two thirds of all new cases were reported in developing countries, among which China accounted for 42% (3).…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al. suggested 6 types of variations in the absence of the CHA; however, the type in which the PHA originates from the SMA, as seen in this case, remains unclassified [6] . Michels divided the anatomic variations in the arterial blood supply to the liver into 10 types and reported that the frequency of the entire hepatic trunk being derived from the SMA (type IX) was 2.5%.…”
Section: Discussionmentioning
confidence: 77%
“…The presence of HA variations was first reported by Haller in 1756 [10] , and several classifications for HA variations have been proposed since [4] , [5] , [6] . The embryologic context of HA is important for understanding how these variants occur.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…They do not originate from a typical position and have replaced a 'usual' artery branch at that location to be the primary blood supply to the corresponding organ or organ section (i.e. the left and right lobes of the liver) [19,22,69]. Knowledge of replaced arteries as variations can be lifesaving for patients with bile duct cancer.…”
Section: Superior Mesenteric Artery Variationsmentioning
confidence: 99%